Values and Learning Processes of Simulation Based on Local Wisdom toward Christian Education Self-reliance in Central Kalimantan - Silipta; Andani Nainggolan (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
The objective of this research is to investigate the nature of Christian education as a set of values transcending the boundaries of other disciplines, including agriculture. Additionally, this research examines the cultural phenomenon of repetition, which may be perceived as meaningful and sustainable. This research method employs field observation, in-depth interviews, and a researcher's immersion in cultural blending. The findings indicate that Christian education can be viewed as a flexible, adaptable value system, particularly when viewed through the lens of Pancasila, a philosophy that emphasizes the unity of humanity, justice, and spirituality. The findings indicate that the learning strategies employed in the context of SMK Pertanian Tumbang Lahang exemplify the values inherent in Christian education, including social sensitivity, responsiveness, care work, ritual, prayer, morality, empowerment, humility, and the cultivation of awareness.